The occurrence of African cassava mosaic virus and East African cassava mosaic Cameroon virus in natural hosts other than cassava in Nigeria - Alabi, O.J.; Ogbe, F.O.; Bandyopadhyay, Ranajit; Dixon, Alfred G.O.; Hughes, J.; Naidu, R.A. (2007)
Cassava mosaic disease (CMD) in Africa is caused by six distinct cassava mosaic viruses (family eminiviridae, genus Begomovirus). Among them, African cassava mosaic virus (ACMV) and East African cassava mosaicCameroon virus (EACMCV) have been reported in CMD-infected cassava plants in Nigeria. Based on PCR tests using virus-specific primers, a leguminous plant Senna occidentalis and the weed Combreturn confertumwere previously identified as natural hosts for ACMV and EACMCV and castor oil plant Ricinus cornmunis as a host for ACMV. In a recent study, we identified a second leguminous plant Leucana leucocephala as a host for ACMV and EACMCV. In order to confirm the PCR results, we have amplified 1 kbp DNA fragments specific to ACI and AV2 open reading frames (OW) of ACMV and AC3 and ACI ORFs of EACMCV. The amplicons were cloned and nucleotide sequences compared with corresponding sequences of ACMV and EACMCV isolates from cassava. All ACMV isolates from the four natural hosts showed sequence identity between 95 and 96 percent with cassava isolates. Similarly, all EACMCV isolates from the three natural hosts showed nucleotide sequence identity above 98 percent with isolates from cassava. The results confirm the natural occurrence of ACMV and EACMCV in four plant species other than cassava and indicate that theymay play a role in the epidemiology of CMD in Nigeria.